Effects of Nd3+-substitution for Bi-site on the leakage current, ferroelectric and dielectric properties of Na0.5Bi0.5TiO3 thin films. Issue 6 (15th April 2018) - Yang, C.H.; Han, Y.J.; Sun, X.S.; Chen, J.; Qian, J.; Chen, L.X.
Abstract: Perovskite Na0.5 (Bi1−x Ndx )0.5 TiO3 (x = 0, 0.01, 0.03, 0.05; xNd: NBT) ferroelectric films were synthesized on indium tin oxide (ITO)/glass substrates via chemical solution deposition. Structural characterization shows the similar phase-pure perovskite structures in all the films and gradually decreased grain sizes with Nd 3+ doping amount increasing. For all the films, the leakage behaviors are dominant by the Ohmic conduction in low electric field region and interface-limited Fowler-Nordheim tunneling mechanism in high electric field region. Additionally, the space-charge-limited conduction is involved in 0.03Nd: NBT sample. Compared with the sample of x = 0, the resistivity can be improved through Nd 3+ -substitution in NBT. Enhanced ferroelectricity can be obtained from the dynamic polarization-electric field test, and the reversible domains switching in film can be confirmed by static dielectric constant-electric field measurement. Especially, the 0.03Nd: NBT possesses optimal electrical performances with a large remanent polarization ( P r = 26.7 μC/cm 2 ) and a high dielectric tunability (19.6% at 100 kHz).